2015
DOI: 10.1111/oik.02529
|View full text |Cite
|
Sign up to set email alerts
|

Extended leaf phenology may drive plant invasion through direct and apparent competition

Abstract: Invasive plants can inflict great harm, yet drivers of successful invasion remain unclear. Many invaders of North American deciduous forests exhibit extended leaf phenology (ELP), or longer growing season relative to natives. ELP may grant invaders competitive advantages, but we argue that ELP more potently drives invasion in the presence of herbivores. ELP invaders can support herbivores by lessening starvation during winter; consequently, native plants may suffer when attacked later through apparent competit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 66 publications
2
13
0
Order By: Relevance
“…In deciduous forests, invasive plant species often have extended leaf phenologies that may confer an advantage to them over neighboring native plant species (Fridley 2012, Smith 2013. Using a mathematical model, Smith and Hall (2016) showed that the combined effect of greater preference by herbivores for native taxa and extended phenology of invasive taxa could significantly increase the performance of the invader and potentially result in the exclusion of the native apparent competitor. Using a mathematical model, Smith and Hall (2016) showed that the combined effect of greater preference by herbivores for native taxa and extended phenology of invasive taxa could significantly increase the performance of the invader and potentially result in the exclusion of the native apparent competitor.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In deciduous forests, invasive plant species often have extended leaf phenologies that may confer an advantage to them over neighboring native plant species (Fridley 2012, Smith 2013. Using a mathematical model, Smith and Hall (2016) showed that the combined effect of greater preference by herbivores for native taxa and extended phenology of invasive taxa could significantly increase the performance of the invader and potentially result in the exclusion of the native apparent competitor. Using a mathematical model, Smith and Hall (2016) showed that the combined effect of greater preference by herbivores for native taxa and extended phenology of invasive taxa could significantly increase the performance of the invader and potentially result in the exclusion of the native apparent competitor.…”
Section: Discussionmentioning
confidence: 99%
“…In a common garden study (see Bhattarai et al 2016), plant genotypes from the invasive lineage sprouted earlier than genotypes of the native lineage (Bhattarai et al unpublished data; see also Park and Blossey 2008), which may result in larger populations of herbivores in early spring that are likely to spillover to plants of the more preferred native lineage. Using a mathematical model, Smith and Hall (2016) showed that the combined effect of greater preference by herbivores for native taxa and extended phenology of invasive taxa could significantly increase the performance of the invader and potentially result in the exclusion of the native apparent competitor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The success of invasive plants can be ascribed to a suite of contributors. Mounting evidence suggests that plant phenology may play a pivotal role in driving plant invasions (Fridley, ; Godoy, Castro‐Diez, Valladares, & Costa‐Tenorio, ; Novy, Flory, & Hartman, ; Rejmánek, ; Smith & Hall, ; Smith & Reynolds, ; Wolkovich & Cleland, ). Harrington, Brown, and Reich () pioneered work in this aspect, and their research has brought renewed interest in the study of plant phenology (Cleland, Chuine, Menzel, Mooney, & Schwartz, ).…”
Section: Introductionmentioning
confidence: 99%